Reading comprehension improvement in autism - Beckerson, Meagan; Paisley, Courtney; Murdaugh, Donna; Holm, Haley; Lemelman, Amy; Spencer, Alyssa; O’Kelley, Sarah; Kana, Rajesh (Frontiers in Psychiatry, 2024)
A subset of autistic children excel at word decoding but have difficulty with reading comprehension (i.e., the discrepant poor comprehender reading profile). Prior research suggests the Visualizing and Verbalizing (V/V) for language comprehension and thinking intervention helps improve reading comprehension in autistic children with this reading profile. Previous studies have demonstrated the role of vocabulary, memory, and social functioning in reading comprehension; however, predictors and moderators of reading comprehension within this specific profile of autistic readers have not been thoroughly explored. In this study, we examined the effectiveness of the V/V intervention by comparing reading comprehension scores between groups and across time. Participants included a sample of autistic children (AUT-EXP; n=22) and a waitlist control group of autistic children (AUT-WLC; n=17) with reading comprehension difficulties, as well as a sample of non-autistic children (Non-AUT; n=26) (all age 8-13 years). AUT-EXP and AUT-WLC groups completed a battery of cognitive assessments during pre and post tests. We also analyzed whether cognitive assessment scores predicted reading comprehension, and examined the moderating effects of group (AUT-EXP vs. AUT-WLC) on these relationships. The AUT-EXP group significantly improved in their pre to post reading comprehension scores (t(21)=4.19, p<.001, d=.89), whereas the AUT-WLC group did not. Verbal memory significantly predicted reading comprehension, though group did not moderate relationships between cognitive test performance and reading comprehension. Results suggest that the V/V intervention may help improve reading comprehension for autistic children with the discrepant poor comprehender reading profile. Additionally, strategies for improving verbal memory may indirectly enhance reading comprehension in autistic children with this reading profile. Key words: Autism, reading comprehension, visualizing/verbalizing, intervention, verbal memory